Psych 8th season - Sorvino, Mira.; Campbell, Bruce; Arnold, Tom.; Devine, Loretta; Hill, Dule.; Roday, James ([United States] : Universal Home Entertainment, 2014)
Case-cracking 'psychic' detective Shawn Spencer and his best friend Burton 'Gus' Guster have their hands full getting to the bottom of crime-filled conundrums around Santa Barbara. From a prestigious paranormal police consultant convention to zombie nightmares, Shawn and Gus need all the help they can get as new hijinks and tests arise for your favorite sleuths in the eighth season. Witness every episode back-to-back and uninterrupted of the hilarious season featuring a gaggle of guest stars.
Tom Arnold, James Roday, Mira Sorvino, Loretta Devine, Bruce Campbell, Dule Hill.
DVD.
English audio.
English subtitles for the deaf and hard of hearing.
107478
Keywords: Private investigators -- Drama; Criminal investigation -- Drama; Photographic memory -- Drama; Psychics -- Drama; Impostors and imposture -- Drama; Police -- Drama; Television series; Comedy; DVDs; Television crime shows; Television comedies; Detective and mystery television programs; Fiction television programs; Video recordings for the hearing impaired